Investment Attractiveness of Enterprises in the Context of Their Economic Security - Pavlova Halyna Ye.; Аtamas Oleksandr Р.; Marykhnich Yevhenii V. (Bìznes Inform, 2023)
The article allocates the previously unresolved parts of the general problem regarding the development of the investment attractiveness of enterprises in the context of its economic security and finds that in connection with the implementation of the goals of sustainable development, which requires additional costs, the the entrepreneur’s profit decreases, which contradicts his interests. The aim of the article is to establish regularities of development of investment attractiveness of enterprises in the context of its economic security. In this study, the authors proceeded from the assumption that the nature of investment processes is consistent with the goals of sustainable development. The main obstacle to studying the issue of investment attractiveness in the context of economic security is that it is impossible to consider only economic factors without also taking into account ecological and social factors that affect development. It is found that «economic security» is a relatively new category of economics which entered scientific circulation only in the first half of the 20th century and which influence at the national level came to consideration in the 1970s. Despite this, even at the beginning of the new millennium, «economic security» failed to become an independent discipline. It is substantiated that the investment value of a corporation can be considered in combination with its financial capacity, development potential, economic and information security, etc., as well as a complex of various factors, the list and weight of which may change along with the investor’s goals. Convincing investors is crucial for the survival and growth of an enterprise, as a stable, investment-oriented business will have a higher degree of success. As a result, it will have a longer period of economic stability, encouraging investors to make a positive decision on long-term investments.